Students touched and moved by UMP volunteers joining house cleaning activities - Nor Salwana, Mohammad Idris (2022)
TEMERLOH, 31 December 2021 - Surprised and moved. Those were the feelings invoked when a group of volunteers from Universiti Malaysia Pahang (UMP) consisting of staff and students suddenly appeared in front of UMP students’ houses to help clean their homes affected by the flood recently.